Perancangan Sistem Informasi Kas Masuk Dan Kas Keluar Berbasis Web Pada Kantor Notaris Krisalia Wahyu Sari Kota Jambi - Gunardi; Ghea Permata Rizky (Journal of Applied Accounting And Business, 2021)
Krisalia Wahyu Sari Notary Office is a medium business unit located at Jln. Otto Iskandardinata No.59, which is engaged in making Authentic Deed regarding all deeds, agreements and provisions required by statutory regulations. The purpose of this study is to analyze the current system, so that it can overcome the problems faced at the Krisalia Wahyu Sari Notary Office of Jambi City, by designing Web-Based Cash In and Out Cash Information System Design at the Krisalia Wahyu Sari Notary Office in Jambi City . As for the constraints faced, company data security is not guaranteed, this is because documents are still in the Form of paper that is easily lost, damaged or lost, the information generated cannot be presented on time because it requires a long time to process data.  The Research Framework that will be carried out in solving the problem discussed is identifying, searching for information based on theoretical foundations, collecting data using observation and interview methods, analyzing to find solutions to the problems faced by Krisalia Wahyu Sari's Notary Office in Jambi City. The method uses the waterfall model, the implementation of this study uses the PHP Language and MySQL DBMS. To produce data processing applications that are expected to facilitate data processing and report generation.